Revealing Resistive Switching of Phase Transitions in an Al‐Doped Single Crystal of VO2 by DC and Pulsed Electrical Measurements - Patlagan, Larisa; Reisner, George M.; Fisher, Bertina (Advanced Physics Research, 2025)
The simple phase diagram of pure VO2 consisting of an insulating monoclinic M1 phase and a metallic tetragonal R phase with a steep insulator‐metal‐transition (IMT) at TIMT = 340 K, is enriched by two additional insulating phases, a triclinic (T) and a monoclinic (M2) and multiple phase transitions, when strained or doped with M3+ions (M = Ga, Al, Cr, Fe, Mg). Under low‐current R(T) measurements, the T(M1 → M2) and IMT are the only once detected by X‐ray diffraction that show reproducible resistive switching (RS) and hysteresis typical of first‐order transitions. Following the surprising detection of the RS associated with the M1→T transition induced by a high electric field in Ga‐, Al‐, and Cr‐doped VO2 crystals, we attempted to uncover those associated with additional transitions in Al‐doped VO2 nanostructures, as reported by Strelcov et al., Nano Letters 2012. Reported herein is the investigation of a single crystal of nominal Al0.01V0.99O2 composition, by repeated direct current (DC) and pulsed IV measurements at fixed ambient temperatures below and at room temperature (RT). RS associated with the various phase transitions appeared in the nonlinear I(V) regime induced by self‐heating (Joule heating), including all those that are absent under low‐electric‐current measurements. RS(T→M2) transition seen on the R inversevs T plot (left). This, and RS associated with additional transitions seen on the oscillogram of a pulsed current (middle)